Arrhythmic Risk Assessment of Hypokalaemia Using Human Pluripotent Stem Cell-Derived Cardiac Anisotropic Sheets - Gurung, Bimal; Tse, Gary; Keung, Wendy; Li, Ronald A.; Wong, Wing Tak (Frontiers in Cell and Developmental Biology, 2021)
Introduction: Hypokalaemia, defined as extracellular concentration of K+ below 3.5 mM, can cause cardiac arrhythmias by triggered or re-entrant mechanisms. Whilst these effects have been reported in animal and human stem cell-based models, to date there has been no investigation in more complex structures such as the human ventricular cardiac anisotropic sheet (hvCAS). Here, we investigated arrhythmogenicity, electrophysiological and calcium transient (CaT) changes induced by hypokalaemia using this bioengineered platform. Methods: An optical mapping technique was applied on hvCAS derived from human pluripotent stem cells to visualize electrophysiological and CaT changes under normokalaemic (5 mM KCl) and hypokalaemic (3 mM KCl) conditions. Results: Hypokalaemia significantly increased the proportion of preparations showing spontaneous arrhythmias from 0/14 to 7/14 (Fisher’s exact test, P = 0.003). Hypokalaemia reduced longitudinal conduction velocity (CV) from 7.81 to 7.18 cm·s–1 (n = 9, 7; P = 0.036), transverse CV from 5.72 to 4.69 cm·s–1 (n = 12, 11; P = 0.030), prolonged action potential at 90% repolarization (APD90) from 83.46 to 97.45 ms (n = 13, 15; P < 0.001), increased action potential amplitude from 0.888 to 1.195 ΔF (n = 12, 14; P < 0.001) and CaT amplitude from 0.76 to 1.37 ΔF (n = 12, 13; P < 0.001), and shortened effective refractory periods from 242 to 165 ms (n = 12, 13; P < 0.001). Conclusions: Hypokalaemia exerts pro-arrhythmic effects on hvCAS, which are associated with alterations in CV, repolarization, refractoriness and calcium handling. These preparations can provide a useful platform for investigating electrophysiological substrates and for arrhythmia screening.